Toward a General Theory of Organizing Volume 1: Introducing the Network Field Model - Peters, Steef; Stephenson, Karen (IntechOpen, 2022)
There are three volumes in this body of work. In Volume 1, we lay the foundation for a general theory of organizing. We propose that organizing is a continuous process of ongoing mutual or reciprocal influence between objects (e.g., human actors) in a field, whereby a field is infinite and connects all the objects in it much like electromagnetic fields influence atomic and molecular charged objects or gravity fields influence inanimate objects with mass such as planets and stars. We use field theory to build what we call the Network Field Model. In this model, human actors are modeled as point-like objects in the field. The influence between and investments in these point-like human objects are explained as energy exchanges (potential and kinetic), which can be described in terms of three different types of capital: financial (assets), human (the individual), and social (two or more humans in a network). This model is predicated on a field theoretical understanding of the world we live in. We use historical and contemporaneous examples of human activity and describe them in terms of the model. In Volume 2, we demonstrate how to apply the model. In Volume 3, we use experimental data to prove the reliability of the model. These three volumes will persistently challenge the reader's understanding of time, position and what it means to be part of an infinite field.